Aural myiasis caused by Parasarcophaga (Liosarcophaga) dux (Thomson) in Thailand - T. Chaiwong (2018)
© 2014 MSPTM All rights reserved. Herein is reported the first case in Thailand of aural myiasis caused by the flesh fly, Parasarcophaga (Liosarcophaga) dux (Thomson). A 5-day-old infant was taken to hospital with a slightly bloody ear. Two fly larvae exiting the ear and another recovered by a physician were alive, and confirmed as P. dux species from adult examination results. This case brought attention to the need for protection against synanthropic flies, particularly for infants and/or hearing impaired patients.